2018
DOI: 10.1186/s13561-018-0203-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capitation payment on utilization and claims expenditure under National Health Insurance Scheme: a cross-sectional study of three regions in Ghana

Abstract: IntroductionGhana introduced capitation payment under National Health Insurance Scheme (NHIS), beginning with pilot in the Ashanti region, in 2012 with a key objective of controlling utilization and related cost. This study sought to analyse utilization and claims expenditure data before and after introduction of capitation payment policy to understand whether the intended objective was achieved.MethodsThe study was cross-sectional, using a non-equivalent pre-test and post-test control group design. We did tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…In 2003, Ghana introduced a NHIS as a measure to safeguard its population against out-pocket-payment at the point of accessing healthcare services [21] particularly maternal healthcare services. It is, however, important to note that the NHIS policy recognises that some sections of the society may not be able to make the minimum contribution to the scheme [22]. As a result, children under 18 years old, elderly above 70 years old, Social Security and National Insurance Trust (SSNIT) pensioners, pregnant women, and extreme poor do not pay the premium [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, Ghana introduced a NHIS as a measure to safeguard its population against out-pocket-payment at the point of accessing healthcare services [21] particularly maternal healthcare services. It is, however, important to note that the NHIS policy recognises that some sections of the society may not be able to make the minimum contribution to the scheme [22]. As a result, children under 18 years old, elderly above 70 years old, Social Security and National Insurance Trust (SSNIT) pensioners, pregnant women, and extreme poor do not pay the premium [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, important to note that the NHIS policy recognises that some sections of the society may not be able to make the minimum contribution to the scheme [22]. As a result, children under 18 years old, elderly above 70 years old, Social Security and National Insurance Trust (SSNIT) pensioners, pregnant women, and extreme poor do not pay the premium [22]. This signals that exemption of pregnant women from paying the premium seeks to do away with financial barriers to maternal healthcare services and thus, to reduce or eradicate pregnancy-related deaths.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies in low- and middle-income (LMIC) settings have explored healthcare providers’ views of—and experiences with—capitation payment schemes ( Agyei-Baffour et al , 2013 ; Andoh-Adjei et al , 2018 ; Sieverding et al , 2018 ; Suchman, 2018 ; Wangai et al , 2019 ), very few have sought to quantify provider preferences for the payment mechanism. A notable exception is Robyn et al (2012) who conducted a DCE among health workers in Burkina Faso to elicit their preferences for the attributes of capitation used in a community-based health insurance (CBHI) scheme.…”
Section: Introductionmentioning
confidence: 99%
“…The payment methods used by states (purchasers) vary across countries ( Witter et al , 2010 , 2016 ; Richard et al , 2013 ; Wang et al , 2017 ; Andoh-Adjei et al , 2018 ). Table 1 summarizes the payment methods used in some African countries with cost-reduction policies.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of these various payment methods on direct medical expenses (the portion of health expenditures usually covered by these policies), and therefore on the sustainability of these policies, have been minimally explored. A before-after controlled study conducted in three regions in Ghana showed that the shift from diagnosis-related groupings to a capitation payment method did not significantly reduce the expenditures for services provided ( Andoh-Adjei et al , 2018 ). In Burkina Faso, a pre-post study comparing the direct medical expenditures associated with deliveries during a case-based reimbursement period to those during a fee-for-service (FFS) reimbursement period in two health districts found that the direct expenditures significantly increased in some health facilities, decreased in others or remained unchanged in a third group.…”
Section: Introductionmentioning
confidence: 99%